2021
DOI: 10.1002/anie.202109237
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterisation of Highly Cooperative FAK‐Degrading PROTACs

Abstract: Focal adhesion kinase (FAK) is ak ey mediator of tumour progression and metastasis.T od ate,c linical trials of FAKi nhibitors have reported disappointing efficacy for oncology indications.W er eport the design and characterisation of GSK215, ap otent, selective,F AK-degrading Proteolysis Targeting Chimera (PROTAC)b ased on ab inder for the VHL E3 ligase and the knownF AK inhibitor VS-4718. Xray crystallography revealed the molecular basis of the highly cooperative FAK-GSK215-VHL ternary complex, and GSK215 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 39 publications
7
68
0
5
Order By: Relevance
“…The last structure we cover is of a CRL2 VHL -recruiting PROTAC degrader of focal adhesion kinase (FAK, also known as PTK2) (120), an important cancer target in solid tumours that is associated with poor clinical outcomes (121,122). FAK-degrading PROTACs active in cellular assays had previously been reported by groups at Yale University (CRL2 VHL -recruiting), Boehringer Ingelheim/University of Dundee (CRL2 VHL -or CRL4 CRBN -recruiting), and Tsinghua University (CRL4 CRBN -recruiting) (123)(124)(125).…”
Section: Protacsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last structure we cover is of a CRL2 VHL -recruiting PROTAC degrader of focal adhesion kinase (FAK, also known as PTK2) (120), an important cancer target in solid tumours that is associated with poor clinical outcomes (121,122). FAK-degrading PROTACs active in cellular assays had previously been reported by groups at Yale University (CRL2 VHL -recruiting), Boehringer Ingelheim/University of Dundee (CRL2 VHL -or CRL4 CRBN -recruiting), and Tsinghua University (CRL4 CRBN -recruiting) (123)(124)(125).…”
Section: Protacsmentioning
confidence: 99%
“…FAK-degrading PROTACs active in cellular assays had previously been reported by groups at Yale University (CRL2 VHL -recruiting), Boehringer Ingelheim/University of Dundee (CRL2 VHL -or CRL4 CRBN -recruiting), and Tsinghua University (CRL4 CRBN -recruiting) (123)(124)(125). Although some have since been shown to be active in mouse models (126)(127)(128), biophysical characterisation of ternary complex formation and structure were lacking prior to work by Law et al (120). In this study, PROTACs were designed based on the FAK inhibitor VS-4718/PND-1186 (129) and the VHL ligand (130) with different linkers.…”
Section: Protacsmentioning
confidence: 99%
“…In detail, this PROTAC molecule in mouse liver was able to degrade FAK at low doses and in a rapid and prolonged manner. This study should be useful for the study of FAK-degradation biology in vivo, confirming that FAK-PROTACs could be potential therapeutic agents to treat FAK-related diseases [ 68 ].…”
Section: Protac Moleculesmentioning
confidence: 65%
“…22 ) based on VS-4718 and VHL ligand. 159 Interestingly, it was confirmed that degrader 95 ( GSK-215 ) which possessed a short and rigid linker generated a highly cooperative ternary complex by SPR and X-ray crystallography data. It induced the degradation of FAK with DC 50 of 1.3 nM in A549 cells and induced cell proliferation inhibition in A549, MCF-7 cells rather than BT474 cells.…”
Section: Protacs Targeting Cancer-related Targetsmentioning
confidence: 89%